2008
DOI: 10.1167/iovs.07-1228
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Fine Structure in Retinopathy of Prematurity: An Adaptive Optics Fourier Domain Optical Coherence Tomography Study

Abstract: The foveas of subjects with a history of mild ROP have significant structural abnormalities that are probably a consequence of perturbations of neurovascular development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
177
6
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(204 citation statements)
references
References 28 publications
13
177
6
8
Order By: Relevance
“…Although we have included four representative disorders associated with foveal hypoplasia we have not applied our grading system in patients with other forms of foveal hypoplasia such as nanophthalmos 19 and retinopathy of prematurity. 20 In our study population we find that VA correlates well with the grade of foveal hypoplasia, however validation of the grading scheme in larger cohorts is necessary.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although we have included four representative disorders associated with foveal hypoplasia we have not applied our grading system in patients with other forms of foveal hypoplasia such as nanophthalmos 19 and retinopathy of prematurity. 20 In our study population we find that VA correlates well with the grade of foveal hypoplasia, however validation of the grading scheme in larger cohorts is necessary.…”
Section: Discussionmentioning
confidence: 62%
“…20 In our study population we find that VA correlates well with the grade of foveal hypoplasia, however validation of the grading scheme in larger cohorts is necessary.…”
Section: Hhmi Author Manuscriptmentioning
confidence: 62%
“…5 OCT has revealed changes not evident on ophthalmoscopy, but these can be compatible with good visual acuity. 6,7,[9][10][11] Authors have questioned the possibility of a non-retinal aetiology for visual deficits, so examination of the choroid is warranted. 1 The choroid serves functions including metabolic support for the RPE and retina, acting as a heat sink, and absorbing excess light.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown shallowing of the foveal depression, thickening of the central macula, and a continuity of inner retinal layers across the fovea in those born severely preterm, often despite normal macular appearance on ophthalmoscopy. [6][7][8][9][10][11][12][13][14] However, these macular changes evident on OCT are still compatible with good visual acuity. 6,7,[9][10][11] This has prompted authors to suggest that other factors might be contributory to the variation in vision seen in these patients.…”
Section: Introductionmentioning
confidence: 98%
“…2 Infantile nystagmus has also been described in association with afferent defects such as foveal hypoplasia, aniridia and iris hypoplasia. 8,9 Foveal hypoplasia is typically associated with PAX6 mutations, 9 albinism 10 and retinopathy of prematurity, 11 whereas atypical forms of foveal hypoplasia have been associated with achromatopsia. [12][13][14] Previous studies have also described foveal hypoplasia as being without an identifiable genetic cause.…”
Section: Introductionmentioning
confidence: 99%